Biogenic silica (BSi) content for the Eemian sediment sequence retrieved from Sokli (Finland) in 2010 - Anna Plikk; Stefan Engels; Maria Fernández-Fernández; Christos Katrantsiotis; Malin E Kylander; Ludvig Löwemark; Sakari Salonen; Minna Väliranta; Karin Helmens (PANGAEA, 2025)
The dataset provides quantifications of biogenic silica (BSi) content for the Eemian sediment sequence retrieved from Sokli (Finland) in 2010. Amounts of BSi are presented as percentage of weight and are presented against both depth (m) and age (ka BP). The BSi dataset provides information on Eemian lake ecosystem productivity (Plikk et al., 2016). A set of 898 1 cc sub-samples from the Eemian diatom gyttja has been analyzed using Fourier Transformed Infra Red Spectrometry (FTIRS) at the Department of Ecology and Environmental Science, Umeå University, Sweden, following Rosén et al. (2010). The analysis was performed on freeze-dried homogenized samples using a VERTEX 70 FTIR Spectrometer (Bruker Optics). All samples were pretreated in order to minimize the spectral variation not related to the sample properties. BSi content was quantified using an independent calibration model for BSi (Meyer-Jacob et al. 2014). Thirty samples were selected for conventional measurements of BSi content and used for validation of the model. The conventional measurements were made at the Alfred Wegener Institute for Polar and Marine Research (Bremerhaven, Germany).